Influence of Two Shoots and Four Shoots Training Techniques on Growth, Yield and Quality of Capsicum under Protected Cultivation (Capsicum annuum var. grossum Sendt.) - Gawade, A. D.; Chandanshive, A. V.; Gaikwad, S. D.; Dhemre, J. K.; Jagdale, Y. L.; Bankar, D. R. (International Journal of Economic Plants, 2025)
The present study was conducted during kharif (June to September, 2022) at the Centre of Excellence for Vegetables, KVK, Malegaon, Baramati, Maharashtra, India to evaluate the interaction effects of three training techniques (two shoots, four shoots and unpruned control) and two capsicum hybrids commercial capsicum hybrid-1 (yellow) and commercial capsicum hybrid-2 (red) on growth, yield and quality under a polyhouse. Among the training techniques, two shoot system significantly influenced plant growth and flowering characteristics. Although unpruned plants produced a higher number of fruits per plant, the four shoot training technique recorded the highest fruit yield per plant, per plot and per hectare. Between the two hybrids, Commercial capsicum hybrid-1 outperformed Commercial capsicum hybrid-2 across all growth, yield and quality parameters. In terms of interaction effects, the two shoot + Commercial capsicum hybrid-1 combination resulted in the tallest plants (179.01 cm), earliest flowering (19.79 days) and earliest 50% flowering (31.07 days). The maximum number of fruits plant-1 (23.71) was observed in unpruned+Commercial capsicum hybrid-1. However, two shoot+Commercial capsicum hybrid-1 recorded highest average fruit weight (198.74 g), polar diameter (10.03 cm), equatorial diameter (9.39 cm) and pericarp thickness (0.90 cm). The four shoot+Commercial capsicum hybrid-1 treatment recorded highest yield plant-1 (2.85 kg), m-2 (17.10 kg), plot-1 (30.51 kg) and (115.98 t) ha-1 with excellent quality fruits. In contrast, the lowest yield was recorded in unpruned +Commercial capsicum hybrid-2. The four shoot training system combined with the Commercial capsicum hybrid-1 proved most effective for maximizing growth, yield and quality of colored capsicum under protected cultivation conditions.